Medicinal Plant Images - Cock, I.E. (Pharmacognosy Communications)
The genus Acacia (family Fabaceae) is a large genus of more than 1200 trees and shrubs which are widely distributed throughout the world, with more than 700 species indigenous to Australia. The Australian species had multiple medicinal uses by indigenous Australians, including being used to treat diarrhoea and hyperglycemia1 and as a general antiseptic agent.2,3 Many Australian Acacia species have been reported to have amtimicrobial, molluskicidal, antihypertensive and platelet aggregator activities.1 This photograph was taken at Griffith University, Australia by Dr Ian Cock.